Woodrow Wilson: ruling elder, spiritual president - Hankins, Barry (Spiritual lives, 2016)
There is a mighty task before us and it welds us together. It is to make the United States a mighty Christian nation and to Christianize the World." The 28th president was not principally a religious figure, and he didn't fit comfortably in any religious camp. In this book Barry Hankins tells the story of Wilson's religion as he moved from the Calvinist orthodoxy of his youth to a progressive, spiritualized religion short on doctrine and long on morality